Laboratory Diagnosis of Enteric Fever: A Review Update - Sultana, Safia; Maruf, Md Abdoullah Al; Sultana, Rabeka; Jahan, Shahanaz (Bangladesh Journal of Infectious Diseases, 2017)
The diagnosis of typhoid fever on clinical presentations alone is difficult, as the presenting symptoms are diverse and similar to those observed with other febrile illnesses, especially during the first weeks of the infection. Therefore, laboratory-based investigations are essential for supporting the diagnosis of the disease. The gold standard for diagnosis of typhoid fever is the isolation of Salmonella typhi from appropriate samples including blood, bone marrow aspirates, stool, urine and rose spots. This facility is not available in many areas where the disease is endemic. Serodiagnosis depends upon the 100-year-old Widal test, and other serological diagnostic tools have limitations because of their low sensitivity and/or specificity. The development of molecular methods for diagnosis of infectious diseases, including typhoid fever has improved the sensitivity and specificity of diagnosis. One of the molecular methods, Polymerase chain reaction (PCR) is the most sensitive and rapid method to detect microbial pathogens in clinical specimens. Antigen detection has not been investigated for well over three decades and detecting an immune response specific for typhoid fever has been done only with antibody detection. There is an urgent need for the rational design and evaluation of effective and appropriate diagnostics for typhoid fever which must include the emerging threat of S. typhi. However, monitoring of antibiotic susceptibility patterns will ensure that signs of developing resistance are detected early and that the appropriate action is taken. Therefore, this present review has been designed to describe the different diagnostic procedure of typhoid fever. Bangladesh Journal of Infectious Diseases 2016;3(2):43-51